An investigation into loss of meaning in the translation process as manifested in the Vietnamese version of the world is flat by Thomas L. Friedman - Trần, Thị Mai Le. (The University of Da Nang, 2011)
Introduction; Literature review and theoretical background; Methods and procedures...